TERMINAL FLOWER1 Functions as a Mobile Transcriptional Cofactor in the Shoot Apical Meristem. Issue 4 (29th January 2020) - Goretti, Daniela; Silvestre, Marina; Collani, Silvio; Langenecker, Tobias; Méndez, Carla; Madueño, Francisco; Schmid, Markus
Abstract : TERMINAL FLOWER1 acts in the shoot apical meristem as a mobile cell-non-autonomous transcriptional cofactor that associates with DNA to regulate meristem indeterminacy and flowering. Abstract: The floral transition is a critical step in the life cycle of flowering plants, and several mechanisms control this finely orchestrated process. TERMINAL FLOWER1 (TFL1) is a floral repressor and close relative of the florigen, FLOWERING LOCUS T (FT). During the floral transition, TFL1 expression is up-regulated in the inflorescence apex to maintain the indeterminate growth of the shoot apical meristem (SAM). Both TFL1 and FT are mobile proteins, but they move in different ways. FT moves from the leaves to the SAM, while TFL1 appears to move within the SAM. The importance of TFL1 movement for its function in the regulation of flowering time and shoot indeterminacy and its molecular function are still largely unclear. Our results using Arabidopsis ( Arabidopsis thaliana ) indicate that TFL1 moves from its place of expression in the center of the SAM to the meristem layer L1 and that the movement in the SAM is required for the regulation of the floral transition. Chromatin immunoprecipitation sequencing and RNA sequencing demonstrated that TFL1 functions as a cotranscription factor that associates with and regulates the expression of hundreds of genes. These newly identified direct TFL1 targets provide the possibility to discover new roles for TFL1 in the regulation of floral transition and inflorescence development.